Integrating Y-Chromosome, Mitochondrial and autosomal data to analyse the origin of pig breeds - Ramírez, O.; Ojeda, A.; Tomas, A.; Gallardo, D.; Huang, L.S.; Folch, J.M.; Clop, A.; Sánchez, A.; Babaoui, B.; Hanotte, Olivier H. (Oxford University Press, 2009)
We have investigated the origin of swine breeds through the joint analysis of mitochondrial, microsatellite and Y-chromosome polymorphisms in a sample of pigs and wild boars with a worldwide distribution. Genetic differentiation between pigs and wild boars was remarkably weak, likely as a consequence of a sustained gene flow between both populations. The analysis of nuclear markers evidenced the existence of a close genetic relationship between Near Eastern and European wild boars making difficult to infer their relative contributions to the gene pool of modern European breeds. Moreover, we have shown that European and Far Eastern pig populations have contributed maternal and paternal lineages to the foundation of African and South American breeds. While West African pigs from Nigeria and Benin exclusively harboured European alleles, Far Eastern and European genetic signatures of similar intensity were detected in swine breeds from Eastern Africa. This region seems to have been a major point of entry of livestock species in the African continent as a result of the Indian Ocean trade. Finally, South American creole breeds had essentially a European ancestry although Asian Y-chromosome and mitochondrial haplotypes were found in a few Nicaraguan pigs. The existence of Spanish and Portuguese commercial routes linking Asia with America might have favoured the introduction of Far Eastern breeds into this continent.